Remineralization ability of different root canal sealers - Raghad A Al-Askary; Wiaam M.O. AL-Ashou; Sawsan H. Al-Jubori (Saudi Dental Journal)
Aims: This research was designed to contrast the biocompatibility and remineralization ability of different sealers (BioRoot, MTA-FillApex and GuttaFlow-Bioseal). Method: Twenty rabbits were used in this study, they were randomly divided into 4 groups equally depending on the observation time“3,7,14, and 28 days” post-implantation. Each rabbit was generally anesthetized,“7cm”long incision was made on the skin of the right and left sides of the ventral aspect of the mandible of each rabbit, 4 bony cavities of approximately“5mm”in depth and“2mm”in diameter (2 cavities on the left side and 2 cavities on the right side of mandible of each rabbit) were made in the cortical surface of the buccal alveolar bone. The sealers mixed depend on manufactural instructions and immediately insert into the prepared cavities (in the right side the BioRoot and MTA-FillApex were placed while on the left side, GuttaFlow-Bioseal was placed in one cavity and the other cavity was left unfilled as control).The same volume of each sealer was placed in the corresponding cavity using disposable syringes. After each observation period, the animals were sacrificed and bone biopsy from the tested area was taken and examined histologically using Olympus light microscopy at“400X”magnification. Results: The obtained data were analyzed through non-parametric statistical tests using SPSS software version“22”.Kruskal-Wallis test and Mann - Whitney test were utilized at“0.05”levels of significance to evaluate the results. GuttaFlow-Bioseal displayed excellent biocompatibility in comparison to other groups indicated by low inflammatory tissue reaction at all evaluation intervals. While the BioRoot group represented better osteo-conductivity although statistically not significant than GuttaFlow-Bioseal group. Conclusion: BioRoot and GuttaFlow-Bioseal showed higher osteo-conductivity and biocompatibility than MTA-FillApex. However, all sealer used in this study were well tolerated by bone tissue and might accelerate bone repair.